(untitled) (Scientific Journal of Research Studies in Future Management, 2025)
Introduction: No organization in the global market can accept losses; Overall Equipment Effectiveness (OEE) plays an important role in optimizing processes by measuring performance and identifying factors that reduce productivity. Using Failure Mode and Effects Analysis (FMEA) allows discovering the root causes of OEE decline and helps improve productivity. Methods: This study was conducted to investigate the correlation between Failure Mode Analysis (FMEA) and Overall Equipment Effectiveness (OEE) in Shetab Kar Company, located in Tehran. The research data included information on the factory production line in 2013 to 2014, and library study and electronic search methods were used to collect data. Descriptive and inferential statistics were used to analyze the data. Findings: The Smirnov-Kolmogrov test was used to examine the normality of the variables. There was a significant difference at the α=0.05 level between the theoretical and empirical distributions. Due to the non-normality of the data, Spearman's non-parametric test was used to calculate the correlation coefficient in this study. There is an inverse correlation between the RPN index obtained from the implementation of FMEA and the overall equipment effectiveness (OEE). The correlation value is -0.649 and has been confirmed with a significance level of 0.000 at the 1 percent error level. Results: The results indicate an inverse correlation between the RPN index obtained from the analysis of potential failure modes (FMEA) and the overall equipment effectiveness (OEE), which varies between 0.649 and 0.815 in different sections of productivity, performance and quality. Also, a direct correlation has been observed in some failure detection parameters that affect the improvement of OEE.